PRAKTIK ARISAN ONLINE SISTEM MENURUN DALAM PERSPEKTIF MASLAHAH PADA ARISAN WAHYUNI SHOP DI DESA MENTIBAR KECAMATAN PALOH - Yasnil Candra; Munadi Munadi; Hatoli Hatoli (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2018)
Wahyuni's Arisan shop is one of the many online social gathering accounts on social media, especially Facebook. The arisan organizes an online arisan with a regular declining system every period and has been running for several years. This descending system of online arisan is different from the general arisan, which in practice does not meet face-to-face. This study aims to find out how the practice of online arisan descends on the Wahyuni ​​Shop arisan in Mentibar Village, Paloh District and how the maslahah review of the online arisan practice with a declining system in the perspective of maslahah at the Wahyuni ​​Shop arisan in Mentibar Village, Paloh District. This type of research is a field research, and to ensure the validity of the data, this research uses primary and secondary data with interview and documentation data collection methods. After the data is collected, then data analysis is carried out using a descriptive analysis approach with a qualitative approach. The results showed that the practice of online social gathering in the Wahyuni ​​shop decreased system using a declining system and numbering instead of lottery, this arisan practice was indicated to be not in accordance with Islamic law. In which there is a system that is different from the social gathering in general, namely the contribution of each member is different (Example: 2,400,000, 2,350,000, decreasing and so on until the last number), besides that there is also an admin fee charged to each member at one time. gathering group. After the admin fee, the arisan admin is also required to get the first turn to get dues from each member of the one group, but after being able to not participate in paying the dues from the beginning until the end of the arisan period in one group. This practice raises doubts about its halalness, besides that there is also usury, gharar and dzalim in these practices because arisan itself uses the Qardh concept in its principles, usury here is because of taking advantage of the existence of principled arisan practices such as Qardh, gharar due to unclear bailout funds, while the dzalim contributions are different. The conclusion that Wahyuni ​​shop's arisan brings a lot of benefits, but that benefit is contrary to texts or arguments, therefore the practice of arisan at Wahyuni ​​shop includes maslahah mulghah, which even though in the above arisan there are many benefits or benefits, but there are several implementations of the above arisan which is not in accordance with the syara' and does not meet the maslahah requirements recommended by Islamic law and does not meet the maslahah criteria desired by the shari'a because it is contrary to the texts or arguments.